Bee Killers, Mallophora bomboides (Wiedemann), Mallophora orcina (Wiedemann), and Malophora nigra Williston (Insecta: Diptera: Asilidae) - Gary J. Steck (EDIS)
Three large predaceous robber flies of the genus Mallophora occur in Florida. Mallophora bomboides (Wiedemann) is known as the "Florida bee killer," M. orcina (Wiedemann) as the "southern bee killer," and M. nigra Williston as the "black bee killer" (Bromley 1950). Two other species have been recorded from Florida: M. rex Bromley and M. chrysomela Bromley. Structurally, there is nothing to distinguish them from M. bomboides (Wiedemann), and they are considered to be color variants of the latter. Also, M. nigra Williston may be merely a wholly-black color variant of M. bomboides (Cole and Pritchard 1964).  This document is EENY-315 (originally published as DPI Entomology Circular No. 366), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: March 2004.